Explaining issues relating to Islamic microfinance sustainability: African perspective - Maouloud, Vatimetou Mokhtar; Kassim, Salina; Aslam, Ejaz; Gazali, Haneffa Muchlis; Othman, Anwar Hasan Abdullah (2019)
Islamic microfinance is an effective tool for poverty alleviation worldwide. Islamic microfinance is a beneficial mode1l that enhances individual’s wellbeing not only for Muslims but also for the non- Muslims well. Thus, the aim of this study is to highlight the main issues encountering the Islamic microfinance institutions related to their effectiveness and durability. This study theoretically value the past prominent literature on Islamic microfinance and find out its existing problems in microfinancing. Islamic microfinance institutions are facing several obstacles to sustain in front of the high competition with the conventional microfinance institutions. Among these hindrances: low market penetration, high cost of transactions, shariah regulations, fund mobilization, risks, performance and profitability all of which are considered among the major barriers of Islamic microfinance development. Thus, Islamic microfinance operators must pay more attention to the factors affecting the sustainability of their institutions to be a durable mechanism to alleviate poverty. This a conceptual paper which provides recommendations and solutions to reduce the effects of these problems so that Islamic microfinance can be more efficient and effective strategy to minimize poverty and inequality.